Water dissociation at the Au/α-Fe2O3(0001) interface - Fuente, Silvia Andrea (2018)
The dissociative adsorption of water on a model catalyst formed by a Au5 cluster attached to the Fe-terminated (0001) surface of hematite (α-Fe2O3) was investigated within the density functional theory including an on-site Coulomb term (DFT + U). A flattened 2D-like structure was employed as supported gold particle. On clean hematite, the water molecule interacts with its O atom directly bound to a surface Fe ion. Conversely, in the most stable adsorption mode on Au5/hematite, it adsorbs in a multi-coordinated fashion at the metal-oxide interface and with one H atom oriented downward. Regarding the dissociative process, the isolated Au5 particle has a poor performance to activate one of the OH bonds (H2O → OH + H). However, when supported on hematite it becomes very active, having an activation barrier of only 0.09 eV. This process is even more favorable than on clean hematite. Thus, a very reactive site emerges at the metal-support interface. In this distinctive site, the water molecule is able to adsorb in a configuration (H-down) wherein one OH bond is strongly activated. An adsorbate-induced modification on the way that the flattened Au5 is anchored to the surface was observed, accompanied with changes in Au charges.